2012
DOI: 10.4049/jimmunol.1200416
|View full text |Cite
|
Sign up to set email alerts
|

Target DNA Sequence Directly Regulates the Frequency of Activation-Induced Deaminase-Dependent Mutations

Abstract: Activation-induced deaminase (AID) catalyses class switch recombination (CSR) and somatic hypermutation (SHM) in B lymphocytes to enhance Ab diversity. CSR involves breaking and rejoining highly repetitive switch (S) regions in the IgH (Igh) locus. S regions appear to be preferential targets of AID. To determine whether S region sequence per se, independent of Igh cis regulatory elements, can influence AID targeting efficiency and mutation frequency, we established a knock-in mouse model by inserting a core Sγ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 78 publications
4
27
3
Order By: Relevance
“…Thus, tethering of AID appears as an intrinsic property of transcribed S regions. However, by contrast to the Bcl6 model where regions flanking the core Sg1 were free of AID targeting 20 , we found a sustained high SHM rate throughout the 2-kb-long Jk region that cannot be fully related to the fact that Igk is a much better AID target than Bcl6 (ref. 29).…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Thus, tethering of AID appears as an intrinsic property of transcribed S regions. However, by contrast to the Bcl6 model where regions flanking the core Sg1 were free of AID targeting 20 , we found a sustained high SHM rate throughout the 2-kb-long Jk region that cannot be fully related to the fact that Igk is a much better AID target than Bcl6 (ref. 29).…”
Section: Discussioncontrasting
confidence: 95%
“…While Igk locus enhancers are likely responsible for AID recruitment onto both promoters of the KIKS locus, the extended SHM shows that the inserted S region structure per se modulates the pattern of AID recruitment. These results are reminiscent to the robust AID targeting recently reported in a model in which the core Sg1 region was inserted in the Bcl6 locus 20 . Thus, tethering of AID appears as an intrinsic property of transcribed S regions.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…We recently demonstrated that AID’s mutagenic activity depends on its target sequence at a non-Ig locus, Bcl6 (39). Thus, we sought to test whether target DNA sequences could disrupt the protective mechanism by modifying the processing manner of AID-initiated lesions at the c-myc locus.…”
Section: Introductionmentioning
confidence: 99%